Developing English Teaching Module Integrated Islamic Values in Islamic Elementary School - Nurfadilah Nasruddin; Rustan; Sukirman (Universitas Islam Negeri Palopo, 2026)
It is necessary to develop a teaching module, which is appropriate with learning strategy for elementary school students where the English learning material is integrated with Islamic values. This research aims to produce an appropriate English teaching module based on the Merdeka curriculum for 4th-grade Islamic elementary school students. This research method uses the Research and Development (R&D) method with the ADDIE model approach, which consists of five stages. namely analysis, design, development, implementation, and evaluation. In the analysis stage, student needs and characteristics are assessed to ensure the module meets relevant learning requirements. The design stage builds on this analysis to create a module aligned with the Merdeka Curriculum and Islamic values. The development is turned into a validated and revised teaching module during development. Implementation is done in actual learning in the classroom, with positive feedback from teachers. Both formative and summative evaluations confirmed the module's alignment with expectations and its value in teaching English integrated with Islamic values. Thus, the module is a practical resource for English teachers in Islamic elementary schools, consistent with the Merdeka Curriculum.This module has been comprehensively designed, tested, and validated to ensure compliance with the Merdeka Curriculum and Islamic principles and successfully implemented in the classroom. Continuous supervision and user feedback are required to improve this teaching module further. Adding training for teachers on the use of the module and further adaptation based on student feedback may increase the effectiveness and relevance of the module in daily learning contexts.